Quantification of Chemical States, Dissociation Constants and Contents of Oxygen-containing Groups on the Surface of Biochars Produced at Different Temperatures - Chen, Zaiming; Xiao, Xin; Chen, Baoliang; Zhu, Lizhong (Environmental science & technology, 2015)
Surface functional groups such as carboxyl play a vital role in the environmental applications of biochar as a soil amendment. However, the quantification of oxygen-containing groups on a biochar surface still lacks systematical investigation. In this paper, we report an integrated method combining chemical and spectroscopic techniques that were established to quantitatively identify the chemical states, dissociation constants (pK a), and contents of oxygen-containing groups on dairy manure-derived biochars prepared at 100–700 °C. Unexpectedly, the dissociation pH of carboxyl groups on the biochar surface covered a wide range of pH values (pH 2–11), due to the varied structural microenvironments and chemical states. For low temperature biochars (≤350 °C), carboxyl existed not only as hydrogen-bonded carboxyl and unbonded carboxyl groups but also formed esters at the surface of biochars. The esters consumed OH– via saponification in the alkaline pH region and enhanced the dissolution of organic matter from biochars. For high temperature biochars (≥500 °C), esters came from carboxyl were almost eliminated via carbonization (ester pyrolysis), while lactones were developed. The surface density of carboxyl groups on biochars decreased sharply with the increase of the biochar-producing temperature, but the total contents of the surface carboxyls for different biochars were comparable (with a difference <3-fold) as a result of the expanded surface area at high pyrolytic temperatures. Understanding the wide pK a ranges and the abundant contents of carboxyl groups on biochars is a prerequisite to recognition of the multifunctional applications and biogeochemical cycling of biochars.